How to be a good reviewer: A step‐by‐step guide for approaching peer review of a scientific manuscript - Ahmad R. Sedaghat; Manuel Bernal‐Sprekelsen; Wytske J. Fokkens; Timothy L. Smith; Michael G. Stewart; Romaine F. Johnson (Laryngoscope Investigative Otolaryngology, 2024)
Abstract Objectives The peer review process is critical to maintaining quality, reliability, novelty, and innovation in the scientific literature. However, the teaching of scientific peer review is rarely a component of formal scientific or clinical training, and even the most experienced peer reviewers express interest in continuing education. The objective of this review article is to summarize the collective perspectives of experienced journal editors about how to be a good reviewer in a step‐by‐step guide that can serve as a resource for the performance of peer review of a scientific manuscript. Methods This is a narrative review. Results A review of the history and an overview of the modern‐day peer review process are provided with attention to the role played by the reviewer, including important reasons for involvement in scientific peer review. The general components of a scientific peer review are described, and a model for how to structure a peer review report is provided. These concepts are also summarized in a reviewer checklist that can be used in real‐time to develop and double‐check one's reviewer report before submitting it. Conclusions Peer review is a critically important service for maintaining quality in the scientific literature. Peer review of a scientific manuscript and the associated reviewer's report should assess specific details related to the accuracy, validity, novelty, and interpretation of a study's results. We hope that this article will serve as a resource and guide for reviewers of all levels of experience in the performance of peer review of a scientific manuscript.